People will be 'cloned' to animate computer games. - Wotjas, Olga (Times Higher Education Supplement, 2001)
Reports on the development of a software to allow animation and games companies to clone real people to create realistic animations by researchers at Glasgow and Edinburgh, Scotland. Function of the software tools; Inclusion of the project in the 'proof of concept' funding for Scottish research; Benefits of the funds.